First report of Osmia (Pyrosmia) Tkalců from India with description of a new species and redescription of Osmia gulmargensis Nurse - Sardar, Sayan; Kazmi, S. I.; Rameshkumar, A. (Zootaxa, 2024)
Osmia (Pyrosmia) Tkalců, previously known only from the Palaearctic region, is reported for the first time from India, specifically from northern India, which marks the confluence of the Palaearctic and Indo-Malayan realms and therefore, has a mixture of species from both. This is the third subgenus of Osmia Panzer after Osmia (Helicosmia) Thomson and Osmia (Osmia s.str.) reported from India. Osmia (Pyrosmia) muelleri sp. nov. is described based on the material deposited in the National Zoological Collection, Zoological Survey of India. The rare and unique osmiine bee with an unusually shaped mandible, Osmia gulmargensis Nurse, is also redescribed and illustrated.